Elevated mepolizumab levels in patients with severe asthma responsive to 1 year’s mepolizumab treatment - Takayasu Nishimaki, MD; Hitoshi Sasano, MD, PhD; Sonoko Harada, PhD; Tomohito Takeshige, MD, PhD; Yuuki Sandhu, MD, PhD; Yuki Tanabe, MD; Kei Matsuno, MD, PhD; Tetsutaro Nagaoka, MD, PhD; Jun Ito, MD, PhD; Ryo Atsuta, MD, PhD; Mayu Ohuchi, PhD; Shigehiro Yagishita, MD, PhD; et al. (Journal of Allergy and Clinical Immunology: Global)
Background: Asthma involves variable airflow limitation and persistent airway inflammation. Eosinophilic asthma, characterized by cytokine-mediated type 2 inflammation, is generally treated with inhaled corticosteroids. However, patients with severe asthma may require biologics, such as mepolizumab, which targets IL-5 and can manage uncontrolled eosinophilic asthma. Objective: We investigated the relationship between serum mepolizumab concentrations and treatment response in patients with severe asthma. Methods: Patients with mepolizumab-treated severe asthma were enrolled onto this prospective cohort study. Baseline assessments were conducted and repeated at 3, 6, and 12 months. Those with response were categorized on the basis of improvements in asthma control test score, lung function, and asthma exacerbations. We quantified the serum concentration of mepolizumab at 3, 6, and 12 months after treatment by liquid chromatography coupled with tandem mass spectrometry. Results: Twenty-five adult patients aged 20 years and older with severe asthma were included in the analysis. Serum mepolizumab concentrations significantly increased at 6 and 12 months compared with those at 3 months, particularly in those with disease that responded to therapy. Furthermore, the relative change in mepolizumab concentration was significantly higher in those with response than in those with no response. Body size parameters were negatively correlated with mepolizumab concentration. In those with response, there were inverse correlations between mepolizumab concentration and baseline body size parameters. Conclusions: The study observed a yearlong increase in mepolizumab concentrations, particularly in those with response, indicating a potential mepolizumab surplus. Correlations between mepolizumab concentrations and baseline characteristics suggested differing mepolizumab requirements between those with response and those with no response. Further research is needed to validate these findings and optimize treatment strategies for patients with severe asthma.